Correlation of Cervical Pap Smear with Cervical Biopsy in Lesions of Cervix - Tiwari, Archana; Khanal, Anupa; Sapkota, Pratima; Karki, Asmita (Journal of Institute of Medicine Nepal, 2024)
Introduction Cervical cancer is the leading cause of mortality for women in underdeveloped nations and the 4th leading cause globally. Pap smears are non-invasive method, but are unable to pinpoint their location. However, cervical biopsies are an invasive but gold standard procedure. Methods An analysis of all pap smears obtained during a one-year period, from April 14, 2022 to April 12, 2023 was carried out in the Department of Pathology, LMC, Palpa. But only the cases that had undergone both pap smear and cervical biopsy were compared. Only 64 of the 337 pap smears that were obtained for cytological analysis also had a biopsy. Results Out of 64 pap smear, 32.81% had normal cytology, 25% had ASC-US, 4.68% had atypical glandular cells, and 9.37% had HSIL. The most pap smears were done on people between the ages of 31 and 40. In 64 biopsies, 23 (35.93%) had HSIL, 20 (31.25%) had LSIL, and 7 (10.93%) had chronic cervicitis, according to the histological diagnosis of biopsies. Four individuals had a cancer diagnosis, including two (3.12%) squamous cell carcinomas and two (3.12%) adenocarcinomas. The Pap smear showed a sensitivity of 25.92%, specificity of 94.59%, PPV of 77.77%, NPV of 63.63%, and a diagnostic accuracy of 65.62%. Conclusion The Pap smear test, had poor sensitivity but good specificity in detecting premalignant and malignant cervical abnormalities. Pap smear is a noninvasive method; however, cervical biopsy is a gold standard but invasive technique.